Association of cigarette and water-pipe smoking with increased visceral adiposity, glycemic intolerance and hematological derangement in Iraqi healthy smokers - Saad Abdulrahman Hussain; Ashwaq Nagemeldeen Abbas; Hussein Saad Abdulrahman; Ahmed Shaalan Deab (Universidade de São Paulo, 2022)
Abstract The present study aims to investigate the impacts of cigarette smoking (CS) and water-pipe smoking (WPS) on the visceral adiposity index (VAI), hematological characteristics, and glycemic tolerance in Iraqi healthy smokers. A total of 528 healthy males from different locations of Baghdad city were allocated to three groups; nonsmokers (176), cigarette smokers (178), and WP smokers (174). Baseline characteristics, anthropometric and hematological markers and were reported. Glycemic control was evaluated using the glucose tolerance test. The evidence of elevated VAI, disrupted hematological markers, and impaired glucose tolerance was significantly (P<0.001) different compared with non-smokers and related to the duration of smoking. The impacts of WPS seem to be significantly greater than CS in certain parameters (hemoglobin, hematocrit, methemoglobin, and 2-hour glucose tolerance values). In conclusion, CS and WPS negatively impacted body fat distribution, glucose tolerance, and hematological markers. There is a positive association between the rate of smoking and obesity, glycemic intolerance in both groups.